POLYMER SULFUR PRODUCTION AND ITS APPLICATIONS (Journal of Universal Science Research, 2026)
Elemental sulfur (S) is a strategic raw material produced in large quantities during oil and gas processing and gas purification (recovery of sulfur from H₂S). Converting this sulfur into value-added products is a relevant and urgent task. According to USGS data, global sulfur production in 2024 amounted to approximately 85 million tons. A significant portion of this volume, when exceeding immediate industrial demand, accumulates in storage, increasing environmental and logistical costs.